Endophthalmitis caused by Pantoea agglomerans: clinical features, antibiotic sensitivities, and outcomes - Venincasa VD (Dove Medical Press, 2015)
Vincent D Venincasa, Ajay E Kuriyan, Harry W Flynn Jr, Jayanth Sridhar, Darlene Miller Department of Ophthalmology, Bascom Palmer Eye Institute, Miller School of Medicine, University of Miami, Miami, FL, USA Purpose: To report the clinical findings, antibiotic sensitivities, and visual outcomes associated with endophthalmitis caused by Pantoea agglomerans.Methods: A consecutive case series of patients with vitreous culture-positive endophthalmitis caused by P. agglomerans from January 1, 1990 to December 31, 2012 at a large university referral center. Findings from the current study were compared to prior published studies.Results: Of the three study patients that were identified, clinical settings included trauma (n=2) and post-cataract surgery (n=1). Presenting visual acuity was hand motion or worse in all three cases. All isolates were sensitive to ceftazidime, gentamicin, imipenem, and fluoroquinolones. All isolates were resistant to ampicillin. Initial treatment strategies were vitreous tap and intravitreal antibiotic injection (n=1) and pars plana vitrectomy with intravitreal antibiotic injection (n=2). At last follow-up, one patient had no light perception vision, while the other two had best-corrected visual acuity of 20/200 and 20/400.Conclusion: All Pantoea isolates were sensitive to ceftazidime, gentamicin, imipenem, and fluoroquinolones. All patients in the current study received at least one intravitreal antibiotic to which P. agglomerans was shown to be sensitive in vitro. In spite of this, the visual outcomes were generally poor.Keywords: ocular infection, trauma, antibiotic resistance